Os sentidos atribuídos à linguagem escrita por crianças do primeiro ano do ensino fundamental - Daros, Thuinie Medeiros Vilela (2014)
This dissertation is a result of research carried out between 2012 and 2014, linked to the Postgraduate Program in Education at the State University of West Paraná. The aim was to address the following question: What meanings do the children assign to written language in the first year of Elementary School? The issue raised here is twofolded: on the one hand, there is the need to address the concepts of language regarding the writing appropriation process in the context of the expansion of compulsory schooling; on the other hand, there is the need to conceive children as social subjects, belonging to social groups, in real conditions of existence. The study is a qualitative research organized into two steps: a) literature review and documentary research, and b) field research. The instrument of data collection consisted of semi-structured interviews and collection of children s drawings, involving 67 children between 5 and 6 years old attending regularly four classes in public schools in Foz do Iguaçu (Paraná, Brazil). The analysis of the research subjects utterances was based on the theoretical framework of Mikhail Bakhtin s Theory of Enunciation, particularly the concepts of verbal interaction, dialogism, polyphony and otherness. In order to understand the ways of thinking that are peculiar to children, the study was based on works by Lev Semenovitch Vigotski and Alexis Leontiev. The results showed that there are different meanings assigned to written language by children in the first year of Elementary School. These different meanings are due to the way the teachers have designed and conducted the teaching of written language, as well as the way they consider the specificities of children in their childhoods. The attempt to understand the meanings assigned to written language in the first year of Elementary School, viewing the child as an active subject in the research process allowed to realize the necessity of education professionals promoting, by means of their teaching practices, discursive interlocutions during the education of written language.